Rrp5p, Noc1p and Noc2p form a protein module which is part of early large ribosomal subunit precursors in S. cerevisiae - Hierlmeier, Thomas; Merl, Juliane; Sauert, Martina; Perez-Fernandez, Jorge; Schultz, Patrick; Bruckmann, Astrid; Hamperl, Stephan; Ohmayer, Uli; Rachel, Reinhard; Jacob, Anja; Hergert, Kristin; Deutzmann, Rainer; et al. (Nucleic acids research, 2013)
Eukaryotic ribosome biogenesis requires more than 150 auxiliary proteins, which transiently interact with pre-ribosomal particles. Previous studies suggest that several of these biogenesis factors function together as modules. Using a heterologous expression system, we show that the large ribosomal subunit (LSU) biogenesis factor Noc1p of Saccharomyces cerevisiae can simultaneously interact with the LSU biogenesis factor Noc2p and Rrp5p, a factor required for biogenesis of the large and the small ribosomal subunit. Proteome analysis of RNA polymerase-I-associated chromatin and chromatin immunopurification experiments indicated that all members of this protein module and a specific set of LSU biogenesis factors are co-transcriptionally recruited to nascent ribosomal RNA (rRNA) precursors in yeast cells. Further ex vivo analyses showed that all module members predominantly interact with early pre-LSU particles after the initial pre-rRNA processing events have occurred. In yeast strains depleted of Noc1p, Noc2p or Rrp5p, levels of the major LSU pre-rRNAs decreased and the respective other module members were associated with accumulating aberrant rRNA fragments. Therefore, we conclude that the module exhibits several binding interfaces with pre-ribosomes. Taken together, our results suggest a co- and post-transcriptional role of the yeast Rrp5p-Noc1p-Noc2p module in the structural organization of early LSU precursors protecting them from non-productive RNase activity.
Gesehen am 10.05.2021
Published: 02 December 2012